Pengaruh Objektivitas, Independensi, Pengetahuan, Pengalaman Kerja dan Integritas Profesi Auditor terhadap Kualitas Pekerjaan Auditor - Rhea Samantha Ayu; Dwi Urip Wardoyo (Syntax Corporation, 2023)
Auditing is an examination that is carried out critically and systematically. Where the party that performs is independent of the financial statements that have been prepared by management as well as bookkeeping records and supporting evidence. Auditing can be regarded as a systematic process for objectively gathering and evaluating evidence about assertions about various economic actions or events to determine the degree of correspondence between these assertions. Audit is a process carried out by an auditor to obtain accurate evidence regarding the economic activity of an entity, this audit process will be carried out to equalize the degree of fairness of an entity's economic activity whether it is in accordance with what has been determined and report the results to interested parties. Public accountants who carry out auditing activities work not only for the benefit of the client but also for other parties who use the audit report. This study aims to determine how much influence auditor objectivity, auditor independence, auditor knowledge, auditor work experience and auditor professional integrity have on the quality of auditor work at Public Accounting Offices throughout the City of Bandung. The method used in this study uses quantitative methods using primary data. The sampling technique used is probability sampling. The research data is taken from statements according to auditors who work at Public Accounting Offices throughout the City of Bandung. This study aims to determine the influence of objectivity, independence, knowledge, work experience and professional integrity on the quality of the work of auditors in Public Accounting Offices throughout the City of Bandung.